An Intersectional Approach to Agricultural Research for Development (AR4D) - Tavenner, Katie; Crane, Todd A.; Bullock, Renee; Galiè, Alessandra; Campos, Hugo; Katothya, Gerald (Springer, 2025)
Originating nearly 40 years ago in black feminist thought, the concept of intersectionality has become established as an analytical lens and social theory to account for and better understand multiple and compounding identities and how they influence discrimination and privilege. Within agricultural research for development (AR4D), intersectional approaches are relatively novel compared to traditional gender and social analyses, and to date there are limited tools and empirical studies in AR4D that have adopted such an approach. Without a strong conceptual and methodological foundation, future intersectional approaches in AR4D risk treating multiple identities as standalone “tick box” variables, and not as a holistic way of understanding and addressing these multiple sources of marginalization. To emphasize the potential value-addition of deeper engagement with intersectionality, this chapter outlines the state-of-the-field on intersectional analyses in AR4D and how they are situated within wider gender mainstreaming in international development. Using an empirical case study on index-based livestock insurance (IBLI) in Northern Kenya, the chapter demonstrates an intersectional analysis in AR4D, based on a new conceptual framework and method (Tavenner et al. Gend Technol Dev 26(3):385–403, 2022). This chapter explores how AR4D can deepen its understanding of intersectionality and the potential integration of this concept in a meaningful way that supports addressing multiple layers of inequalities and marginalization in agricultural research methods and practice.